Correction to: Practical considerations for trace DNA recovery and detection of an invasive reptile across different deposition scenarios - Nathan Deliveyne; Tiara Kinanti Benyamin; Jeremy J. Austin; Kate Sanders; Phillip Cassey (Conservation Genetics Resources, 2025)

Practical considerations for trace DNA recovery and detection of an invasive reptile across different deposition scenarios - Nathan Deliveyne; Tiara Kinanti Benyamin; Jeremy J. Austin; Kate Sanders; Phillip Cassey (Conservation Genetics Resources, 2025)
Trace DNA detection methods are increasingly applied to biomonitoring, in conservation, biosecurity, and wildlife forensic sciences. Reptiles are high risk invasive alien species that can cause damaging environmental impacts, yet the dynamics around terrestrial reptile DNA deposition and subsequent detection are poorly understood. Concerns around the role of the pet trade in introducing key reptile pests have resulted in calls for greater biosecurity surveillance and biomonitoring tools. Emerging studies have explored the applications of trace DNA and environmental DNA (eDNA) to reptile detectability, but questions remain around DNA persistence, sample storage, and DNA degradation through time influencing biosecurity compliance uptake. Here we consider Pantherophis guttatus (American corn snake), a key vertebrate pest species in Australia, as a model organism for the study of trace DNA detection over time. Our study focussed on the application of a recently developed corn snake LAMP assay for DNA detection from biosecurity relevant samples, with a particular focus on wildlife compliance for captive reptiles and shed skin samples subject to varied storage and environmental conditions. Experiments were conducted with (i) shed skin subject to a range of storage and treatment conditions over a 10-week period, (ii) trace DNA samples deposited on newspaper, plastic, glazed terracotta, and glass for 0 to 168 h post live snake presence, and (iii) shed skin samples subject to varying environmental conditions over an 8-week period. DNA remained detectable for up to 10 weeks under different storage conditions when extracted from shed skin and for up to 168 h after live reptile contact. DNA extracted from shed skin samples subject to varied environmental conditions was detectable up to 8-weeks post deposition with increasing times to detection. Our findings strengthen the case for trace DNA detection methods being applied to monitoring of terrestrial snakes, particularly for rapid compliance, monitoring, and environmental biosecurity.

Quantifying sedimentary ’blue carbon’ in relation to canopy cover in the seagrass meadows of Turneffe Atoll, Belize - Stacey L. Felgate; Richard Sanders; Valdemar Andrade; Christopher D. G. Barry; Hannah Brittain; Stephen Carpenter; Abel Carrias; Eliceo Cobb; Chris D. Evans; James Hunt; Anna Lichtschlag; Daniel J. Mayor; et al. (Frontiers in Marine Science, 2024)
Introduction Seagrass sediments are important ‘blue carbon’ reservoirs which store climatically significant quantities of organic carbon (C org ) at the global scale. Seagrass meadows that overly these sediments also provide a range of critical ecosystem services including shoreline stabilization, storm surge protection, and fisheries nursery grounds. However, the controls over accumulation and the sources of organic C to these sediments beds are highly variable and poorly understood with the relative importance of hydrodynamic setting, species composition and canopy density being unclear. Methods Here we address these questions using the first observation-based estimates of C org stocks and provenance on Turneffe Atoll, Belize, made via remotely-sensed habitat extent, local C org data and isotopic data. Sedimentary C org was highest in sediments underlying the most sheltered meadows and decreased with increasing exposure to wind and wave energy with the seagrass meadows in the central lagoon containing an extensive deposit of mangrove derived organic carbon, stabilized and protected by the overlying seagrass meadow. Results The influence of species composition appeared weak with the ubiquitous species T. testudinum occurring across a wide range of hydrodynamic regimes ranging from the most sheltered to the most energetic and being associated with a wide range of sedimentary organic C concentrations. Importantly from the perspective of remote sensing, org C concentrations were unrelated to canopy density. We hypothesize that this decoupling of organic C concentration from seagrass canopy cover reflects a much longer timescale for carbon storage in the sediments than the lifespan of the seagrass plants themselves and/or a substantial non seagrass derived organic C burden in seagrass sediments. Overall, we conservatively estimate that the top 30cm of sediments underlying the seagrass meadows overlying carbonate sediments on the atoll exterior store 0.58 x 10 6 Mg C org , most of which is seagrass-derived, whilst the sediments underlying the meadows within the central lagoon store an additional 1.28 x 10 6 Mg C org . When the maximum possible extent of seagrass is considered, this estimate increases to 3.54 x 10 6 Mg C org. Substantial C org stocks extending >1m depth were observed across all sites, and so these inventories are considered conservative. Discussion A preliminary ‘cost of loss’ for sedimentary C org in the top 30 cm of Turneffe Atoll’s seagrass meadows, based on a carbon trading value of €60 tCO 2 (eq), is estimated at €42 million for the outer atoll, increasing to €136 million when the mangrove-derived sediments of the central atoll are considered and €260 million when turbid areas are assumed to contain seagrass.

Warming reduces trophic diversity in high‐latitude food webs - Michelle C. Jackson; Eoin J. O'Gorman; Bruno Gallo; Sarah F. Harpenslager; Kate Randall; Danielle N. Harris; Hannah Prentice; Mark Trimmer; Ian Sanders; Alex J. Dumbrell; Tom C. Cameron; Katrin Layer‐Dobra; et al. (Global Change Biology, 2024)
The physical effects of climate warming have been well documented, but the biological responses are far less well known, especially at the ecosystem level and at large (intercontinental) scales. Global warming over the next century is generally predicted to reduce food web complexity, but this is rarely tested empirically due to the dearth of studies isolating the effects of temperature on complex natural food webs. To overcome this obstacle, we used ‘natural experiments’ across 14 streams in Iceland and Russia, with natural warming of up to 20°C above the coldest stream in each high‐latitude region, where anthropogenic warming is predicted to be especially rapid. Using biomass‐weighted stable isotope data, we found that community isotopic divergence (a universal, taxon‐free measure of trophic diversity) was consistently lower in warmer streams. We also found a clear shift towards greater assimilation of autochthonous carbon, which was driven by increasing dominance of herbivores but without a concomitant increase in algal stocks. Overall, our results support the prediction that higher temperatures will simplify high‐latitude freshwater ecosystems and provide the first mechanistic glimpses of how warming alters energy transfer through food webs at intercontinental scales.

Challenges of regulating commercial use of marine elapid snakes in the Indo‐Pacific - Mark Auliya; Arne Redsted Rasmussen; Kate L. Sanders; Aaron Savio Lobo (Conservation Biology, 2024)
Marine elapid snakes are a diverse, predominantly Indo‐West Pacific species group. The persistent removal of some species has an unquantified but potentially dire impact on populations. We conducted the first comprehensive review of the trade in marine elapid snakes based on published literature (1974–2022) and trade data from the only species (i.e., Hydrophis [ Lapemis ] curtus ) whose trade is monitored internationally. Some species and populations were subjected to targeted harvest for their meat and skins for at least the last century; fisheries are possibly the most significant threat to populations of marine elapids, with the highest numbers being exploited either accidentally, incidentally, or opportunistically in Southeast Asian fisheries targeting other seafood, including demersal trawl and squid fisheries. Southeast Asia is the core region for exploitation of marine elapids. Annual offtake is >225,000 individuals of at least 8 species in the Gulf of Thailand. Of 72 recognized marine elapids (all non‐CITES [Convention on International Trade in Endangered Species of Wild Fauna and Flora] species), Hydrophis curtus and Hydrophis cyanocinctus dominate the skin trade. Skins of H. curtus are traded mainly in East and Southeast Asia and, to some extent, Europe. Despite some baseline information on the trade of these species, the sustainability of their harvests, particularly in the context of the burgeoning and unmanaged nature of fisheries in the region, remains the major challenge. In an era of declining fish stocks, there has been an increasing trend to commercialize the harvest and use marine elapids that were once considered accidental bycatch and discarded. This trend will continue to pose a significant risk to these snakes unless appropriate fisheries and trade regulations are enforced. Applying the precautionary principle to prevent the overexploitation of sea snakes is an indispensable measure in which trade in regional populations should be regulated through CITES. Accordingly, management plans to identify core distribution regions of exploited species would be crucial for assigning national responsibilities to sustain species and populations in the long term.

Ponto-Caspian amphipod co-location with zebra mussel beds (Dreissena polymorpha) is influenced by substrate size and population source - Catherine H. Sanders; Phil L. Buckley; Charlotte Devereux Hunt; Kate L. Mathers; Daniel N. Mills (Hydrobiologia, 2024)
The global spread of non-native species is leading to an increasing frequency of multiple co-occurring non-native species. We examined the co-occurrence of the bivalve mollusc Dreissena polymorpha (zebra mussel) with three Ponto-Caspian amphipods ( Dikerogammarus villosus , Dikerogammarus haemobaphes , and Chelicorophium curvispinum ) across England and Wales in association with in-situ substrate size. For all three amphipod species, substrate grain size where amphipods co-occurred with D. polymorpha was significantly finer than when recorded in isolation. Subsequently, we confirmed this via aquarium experiments. We examined the occurrence of D. villosus with D. polymorpha when present with cobbles, gravel, or sand from three population sources (co-location with abundant D. polymorpha populations, co-location with low populations, and naïve). Experiments demonstrated that D. villosus actively sought shelter on or near D. polymorpha, with their co-location being significantly more prevalent in finer grained substrates (sand > gravel > cobble). The strength of this co-location differed by population source, with those co-located with high D. polymorpha densities demonstrating a greater association. Our analyses and experiments indicate that D. polymorpha may facilitate Ponto-Caspian amphipod establishment in otherwise suboptimal locations, whereby mussel shells provide favourable structural habitat for the amphipods, analogous to the presence of coarse-grained benthic sediment.

The long-term dynamics of invasive signal crayfish forcing of fluvial sediment supply via riverbank burrowing - Catherine H. Sanders; Stephen P. Rice; Paul J. Wood; Kate L. Mathers (Geomorphology, 2023)

Pinpointing Drivers of Extirpation in Sea Snakes: A Synthesis of Evidence From Ashmore Reef - Ruchira Somaweera; Vinay Udyawer; Michael L. Guinea; Daniela M. Ceccarelli; Rohan H. Clarke; Michelle Glover; Mathew Hourston; John Keesing; Arne Redsted Rasmussen; Kate Sanders; Richard Shine; Damian P. Thomson; et al. (Frontiers in Marine Science, 2021)
Over the past decade, vertebrate populations globally have experienced significant declines in distribution and abundance. Understanding the reasons behind these population declines is the first step in implementing appropriate management responses to improve conservation outcomes. Uncovering drivers of extirpation events after the fact, however, requires a careful forensic approach to prevent similar declines elsewhere. The once abundant and species-rich sea snake fauna of Ashmore Reef Marine Park, in the Timor Sea, collapsed dramatically in the early 2000s. No such decline has occurred on surrounding reefs. We synthesise the evidence for this collapse and the subsequent slow recovery and evaluate the plausibility of potential drivers for the declines, as well as provide evidence against certain explanations that have been proposed in the past. Our systematic review shows that of seven possible hypotheses considered, at least three are credible and require additional information: (1) stochastic environmental events may have increased the snakes’ susceptibility to pathogens, (2) a resurgence in the abundance of top predators may have induced a localised change in trophic structure, and (3) an acute increase in local boat traffic may have had negative physical impacts. One or more of these factors, possibly acting in combination with as yet other unidentified factors, is the most plausible explanation for the precipitous decline in sea snake populations observed. Based on this position, we identify future research directions with a focus on addressing critical gaps in knowledge to inform and prioritise future management actions.

Demographic analyses of marine and terrestrial snakes (Elapidae) using whole genome sequences - Alastair J. Ludington; Kate L. Sanders (Molecular Ecology, 2021)
The question of whether spatial aspects of evolution differ in marine versus terrestrial realms has endured since Ernst Mayr's 1954 essay on marine speciation. Marine systems are often suggested to support larger and more highly connected populations, but quantitative comparisons with terrestrial systems have been lacking. Here, we compared the population histories of marine and terrestrial elapid snakes using the pairwise sequentially Markovian coalescent (PSMC) model to track historical fluctuations in species’ effective population sizes ( N e ) from individual whole‐genome sequences. To do this we generated a draft genome for the olive sea snake ( Aiysurus laevis ) and analysed this alongside six published elapid genomes and their sequence reads (marine species Hydrophis curtus , H. melanocephalus and Laticauda laticaudata ; terrestrial species Pseudonaja textilis, Naja Naja and Notechis scutatus ). Counter to the expectation that marine species should show higher overall N e and less pronounced fluctuations in N e , our analyses reveal demographic patterns that are highly variable among species and do not clearly correspond to major ecological divisions. At deeper time intervals, the four marine elapids appear to have experienced relatively stable N e , while each terrestrial species shows a prominent upturn in N e starting at ~4 million years ago (Ma) followed by an equally strong decline. However, over the last million years, all seven species show strong and divergent fluctuations. Estimates of N e in the most recent intervals (~10 kya) are lowest in two of four marine species ( H. melanocephalus and Laticauda ), and do not correspond to contemporary range sizes in marine or terrestrial taxa.

Phototactic tails: Evolution and molecular basis of a novel sensory trait in sea snakes - Jenna M. Crowe‐Riddell; Bruno F. Simões; Julian C. Partridge; David M. Hunt; Steven Delean; Julian G. Schwerdt; James Breen; Alastair Ludington; David J. Gower; Kate L. Sanders (Molecular Ecology, 2019)
Dermal phototaxis has been reported in a few aquatic vertebrate lineages spanning fish, amphibians and reptiles. These taxa respond to light on the skin of their elongate hind‐bodies and tails by withdrawing under cover to avoid detection by predators. Here, we investigated tail phototaxis in sea snakes (Hydrophiinae), the only reptiles reported to exhibit this sensory behaviour. We conducted behavioural tests in 17 wild‐caught sea snakes of eight species by illuminating the dorsal surface of the tail and midbody skin using cold white, violet, blue, green and red light. Our results confirmed phototactic tail withdrawal in the previously studied Aipysurus laevis , revealed this trait for the first time in A. duboisii and A. tenuis , and suggested that tail photoreceptors have peak spectral sensitivities between blue and green light (457–514 nm). Based on these results, and an absence of photoresponses in five Aipysurus and Hydrophis species, we tentatively infer that tail phototaxis evolved in the ancestor of a clade of six Aipysurus species (comprising 10% of all sea snakes). Quantifying tail damage, we found that the probability of sustaining tail injuries was not influenced by tail phototactic ability in snakes. Gene profiling showed that transcriptomes of both tail skin and body skin lacked visual opsins but contained melanopsin ( opn4x ) in addition to key genes of the retinal regeneration and phototransduction cascades. This work suggests that a nonvisual photoreceptor (e.g., Gq rhabdomeric) signalling pathway underlies tail phototaxis, and provides candidate gene targets for future studies of this unusual sensory innovation in reptiles.

Future Directions in the Research and Management of Marine Snakes - Vinay Udyawer; Peter Barnes; Xavier Bonnet; François Brischoux; Jenna M. Crowe-Riddell; Blanche D’Anastasi; Bryan G. Fry; Amber Gillett; Claire Goiran; Michael L. Guinea; Harold Heatwole; Michelle R. Heupel; et al. (Frontiers in Marine Science, 2018)

A finite element model to assess transtibial prosthetic sockets with elastomeric liners - John C. Cagle; Per G. Reinhall; Kate J. Allyn; Jake McLean; Paul Hinrichs; Brian J. Hafner; Joan E. Sanders (Medical & Biological Engineering & Computing, 2018)

Evaluating the drivers of Indo‐Pacific biodiversity: speciation and dispersal of sea snakes (Elapidae: Hydrophiinae) - Kanishka D. B. Ukuwela; Michael S. Y. Lee; Arne R. Rasmussen; Anslem de Silva; Mumpuni; Bryan G. Fry; Parviz Ghezellou; Mohsen Rezaie‐Atagholipour; Kate L. Sanders (Journal of Biogeography, 2016)
Aim There are several competing hypotheses to explain the high species richness of the Indo‐Australian Archipelago ( IAA ) marine biodiversity hotspot centred within Southeast (SE) Asia. We use phylogenetic methods to provide a novel perspective on this problem using viviparous sea snakes, a group with high species richness in the IAA that is highly distinct from other taxa previously studied, both phylogenetically (Reptilia, Amniota) and biologically (e.g. viviparity and direct development). Location Indian Ocean and the West Pacific. Methods We used likelihood and Bayesian methods to reconstruct a multi‐locus time‐calibrated phylogeny for c. 70% of viviparous sea snake species, many sampled from multiple localities in Australasia, Southeast Asia and the Indian Ocean. We then compared rates and temporal concordance of inferred vicariance and dispersal events between marine basins using several approaches including new Bayesian analyses that allow for clade‐specific and event‐specific dispersal rates. Results Phylogenetic analyses and novel Bayesian biogeographical reconstructions indicate that viviparous sea snakes underwent rapid speciation after colonizing SE Asia c. 3 million years ago. Most of the SE Asian sea snake diversity is the result of in situ speciation, most consistent with the ‘centre of origin’ and ‘centre of refuge’ models for biodiversity hotspots. There is also speciation at the periphery, or entirely outside SE Asia; however, contrary to predictions of the ‘accumulation’ and ‘overlap’ models, these new outlying taxa do not preferentially disperse back into SE Asia. Instead, lineages are equally likely to disperse either into or away from SE Asia. Main conclusion The high diversity of sea snakes in SE Asia (and hence the IAA ) is mostly explained by in situ speciation rather than accumulation or overlap. Most speciation events are contemporaneous with sea level changes that generated and dissolved barriers between marine basins during the last 2.5 million years.

Multilocus phylogeography of the sea snake H ydrophis curtus reveals historical vicariance and cryptic lineage diversity - Kanishka D. B. Ukuwela; Anslem de Silva; Mumpuni; Bryan G. Fry; Kate L. Sanders (Zoologica Scripta, 2014)
The I ndo‐ A ustralian archipelago ( IAA ) supports the world's highest diversity of marine fish, invertebrates and reptiles. Many of the marine fish and invertebrates show congruent phylogeographic patterns, supporting a view that the region's complex geo‐climatic history has played an important role in generating its exceptional biodiversity. Here, we examine population genetic structure of the viviparous sea snake, H ydrophis curtus , to assess how past and present barriers to gene flow in the IAA have contributed to genetic and species diversity in a fully marine reptile. Mitochondrial and anonymous nuclear sequences and ten microsatellite loci were used to identify patterns of historical genetic structure and population expansion, reconstruct dated genealogies and assess levels of recent gene flow. These markers revealed strong concordant geographic structure within H . curtus with a prominent genetic break between populations broadly distributed in the I ndian O cean and the W est P acific. These populations were estimated to have diverged in the late P liocene or early P leistocene, and microsatellite admixture analyses suggested limited recent gene flow between them despite the current lack of barriers to dispersal, indicating possible cryptic species. Subsequent divergence in the mid–late Pleistocene was detected within the W est P acific clade among the populations in the P huket‐ T hailand region, S outh‐ E ast A sia and A ustralia, and two of these populations also showed genetic signals of recent range expansions. Our results show that climatic fluctuations during the P lio‐ P leistocene generated high levels of cryptic genetic diversity in H . curtus , and add to similar findings for diverse other marine groups in the IAA .

Recent rapid speciation and ecomorph divergence in I ndo‐ A ustralian sea snakes - Kate L. Sanders; Arne R. Rasmussen; Mumpuni; Johan Elmberg; Anslem de Silva; Michael L. Guinea; Michael S. Y. Lee (Molecular Ecology, 2013)
The viviparous sea snakes ( H ydrophiinae) are a young radiation of at least 62 species that display spectacular morphological diversity and high levels of local sympatry. To shed light on the mechanisms underlying sea snake diversification, we investigated recent speciation and eco‐morphological differentiation in a clade of four nominal species with overlapping ranges in Southeast Asia and Australia. Analyses of morphology and stomach contents identified the presence of two distinct ecomorphs: a ‘macrocephalic’ ecomorph that reaches >2 m in length, has a large head and feeds on crevice‐dwelling eels and gobies; and a ‘microcephalic’ ecomorph that rarely exceeds 1 m in length, has a small head and narrow fore‐body and hunts snake eels in burrows. Mitochondrial sequences show a lack of reciprocal monophyly between ecomorphs and among putative species. However, individual assignment based on newly developed microsatellites separated co‐distributed specimens into four significantly differentiated clusters corresponding to morphological species designations, indicating limited recent gene flow and progress towards speciation. A coalescent species tree (based on mitochondrial and nuclear sequences) and isolation‐migration model (mitochondrial and microsatellite markers) suggest between one and three transitions between ecomorphs within the last approximately 1.2 million to approximately 840 000 years. In particular, the macrocephalic ‘eastern’ population of Hydrophis cyanocinctus and microcephalic H. melanocephalus appear to have diverged very recently and rapidly, resulting in major phenotypic differences and restriction of gene flow in sympatry. These results highlight the viviparous sea snakes as a promising system for speciation studies in the marine environment.

The status of Eurostus dussumierii and Hypsirhina chinensis (Reptilia, Squamata, Serpentes): with comments on the origin of salt tolerance in homalopsid snakes - A. Biju Kumar; Kate L. Sanders; Sanil George; John C. Murphy (Systematics and Biodiversity, 2012)

Isolation, via 454 sequencing, characterisation and transferability of twelve microsatellite loci for Hydrophis spiralis, the yellow sea snake (Serpentes: Elapidae) - Kate L. Sanders; Michael G. Gardner (Conservation Genetics Resources, 2012)

Arthropod molecular divergence times and the Cambrian origin of pentastomids - Kate L. Sanders; Michael S. Y. Lee (Systematics and Biodiversity, 2010)

Molecular evidence for Gondwanan origins of multiple lineages within a diverse Australasian gecko radiation - Paul M. Oliver; Kate L. Sanders (Journal of Biogeography, 2009)
Aim Gondwanan lineages are a prominent component of the Australian terrestrial biota. However, most squamate (lizard and snake) lineages in Australia appear to be derived from relatively recent dispersal from Asia ( in situ diversification, subsequent to the isolation of Australia from other Gondwanan landmasses. We test the hypothesis that the Australian radiation of diplodactyloid geckos (families Carphodactylidae, Diplodactylidae and Pygopodidae), in contrast to other endemic squamate groups, has a Gondwanan origin and comprises multiple lineages that originated before the separation of Australia from Antarctica. Location Australasia. Methods Bayesian ( beast ) and penalized likelihood rate smoothing (PLRS) ( r 8 s ) molecular dating methods and two long nuclear DNA sequences ( RAG‐1 and c‐ mos ) were used to estimate a timeframe for divergence events among 18 genera and 30 species of Australian diplodactyloids. Results At least five lineages of Australian diplodactyloid geckos are estimated to have originated > 34 Ma (pre‐Oligocene) and basal splits among the Australian diplodactyloids occurred c . 70 Ma. However, most extant generic and intergeneric diversity within diplodactyloid lineages appears to post‐date the late Oligocene ( Main conclusions Basal divergences within the diplodactyloids significantly pre‐date the final break‐up of East Gondwana, indicating that the group is one of the most ancient extant endemic vertebrate radiations east of Wallace’s Line. At least five Australian lineages of diplodactyloid gecko are each as old or older than other well‐dated Australian squamate radiations (e.g. elapid snakes and agamids). The limbless Pygopodidae (morphologically the most aberrant living geckos) appears to have radiated before Australia was occupied by potential ecological analogues. However, in spite of the great age of the diplodactyloid radiation, most extant diversity appears to be of relatively recent origin, a pattern that is shared with other Australian squamate lineages.

Pollen‐based reconstructions of biome distributions for Australia, Southeast Asia and the Pacific (SEAPAC region) at 0, 6000 and 18,000 14 C yr BP - Elizabeth J. Pickett; Sandy P. Harrison; Geoff Hope; Kate Harle; John R. Dodson; A. Peter Kershaw; I. Colin Prentice; John Backhouse; Eric A. Colhoun; Donna D'Costa; John Flenley; John Grindrod; et al. (Journal of Biogeography, 2004)
Aim This paper documents reconstructions of the vegetation patterns in Australia, Southeast Asia and the Pacific (SEAPAC region) in the mid‐Holocene and at the last glacial maximum (LGM). Methods Vegetation patterns were reconstructed from pollen data using an objective biomization scheme based on plant functional types. The biomization scheme was first tested using 535 modern pollen samples from 377 sites, and then applied unchanged to fossil pollen samples dating to 6000 ± 500 or 18,000 ± 1000 14 C yr bp . Results 1. Tests using surface pollen sample sites showed that the biomization scheme is capable of reproducing the modern broad‐scale patterns of vegetation distribution. The north–south gradient in temperature, reflected in transitions from cool evergreen needleleaf forest in the extreme south through temperate rain forest or wet sclerophyll forest (WSFW) and into tropical forests, is well reconstructed. The transitions from xerophytic through sclerophyll woodlands and open forests to closed‐canopy forests, which reflect the gradient in plant available moisture from the continental interior towards the coast, are reconstructed with less geographical precision but nevertheless the broad‐scale pattern emerges. 2. Differences between the modern and mid‐Holocene vegetation patterns in mainland Australia are comparatively small and reflect changes in moisture availability rather than temperature. In south‐eastern Australia some sites show a shift towards more moisture‐stressed vegetation in the mid‐Holocene with xerophytic woods/scrub and temperate sclerophyll woodland and shrubland at sites characterized today by WSFW or warm‐temperate rain forest (WTRF). However, sites in the Snowy Mountains, on the Southern Tablelands and east of the Great Dividing Range have more moisture‐demanding vegetation in the mid‐Holocene than today. South‐western Australia was slightly drier than today. The single site in north‐western Australia also shows conditions drier than today in the mid‐Holocene. Changes in the tropics are also comparatively small, but the presence of WTRF and tropical deciduous broadleaf forest and woodland in the mid‐Holocene, in sites occupied today by cool‐temperate rain forest, indicate warmer conditions. 3. Expansion of xerophytic vegetation in the south and tropical deciduous broadleaf forest and woodland in the north indicate drier conditions across mainland Australia at the LGM. None of these changes are informative about the degree of cooling. However the evidence from the tropics, showing lowering of the treeline and forest belts, indicates that conditions were between 1 and 9 °C (depending on elevation) colder. The encroachment of tropical deciduous broadleaf forest and woodland into lowland evergreen broadleaf forest implies greater aridity. Main conclusions This study provides the first continental‐scale reconstruction of mid‐Holocene and LGM vegetation patterns from Australia, Southeast Asia and the Pacific (SEAPAC region) using an objective biomization scheme. These data will provide a benchmark for evaluation of palaeoclimate simulations within the framework of the Palaeoclimate Modelling Intercomparison Project.